Neutralization against BA.2.75.2, BQ.1.1, and XBB from mRNA Bivalent Booster - Davis-Gardner, Meredith E.; Lai, Lilin; Wali, Bushra; Samaha, Hady; Solis, Daniel; Lee, Matthew; Porter-Morrison, Andrea; Hentenaar, Ian T.; Yamamoto, Fumiko; Godbole, Sucheta; Liu, Yuan; Douek, Daniel C.; et al. (The New England journal of medicine, 2023)
One or two monovalent vaccine boosters showed a large decrease in neutralization activity against omicron subvariants. The BA.5-containing bivalent booster improved neutralizing activity against all omicron subvariants.